Sleep phenotype of individuals with autism spectrum disorder bearing mutations in the PER2 circadian rhythm gene. Issue 4 (20th January 2021) - Hoang, Ny; Yuen, Ryan K.C.; Howe, Jennifer; Drmic, Irene; Ambrozewicz, Patricia; Russell, Carolyn; Vorstman, Jacob; Weiss, Shelly K.; Anagnostou, Evdokia; Malow, Beth A.; Scherer, Stephen W.
Abstract: The Per family of genes functions as a primary circadian rhythm maintenance in the brain. Mutations in PER2 are associated with familial advanced sleep‐phase syndrome 1 (FASPS1), and recently suggested in delayed sleep phase syndrome and idiopathic hypersomnia. The detection of PER2 variants in individuals with autism spectrum disorder (ASD) and without reported sleep disorders, has suggested a role of circadian‐relevant genes in the pathophysiology of ASD. It remains unclear whether these individuals may have, in addition to ASD, an undiagnosed circadian rhythm sleep disorder. The MSSNG database was used to screen whole genome sequencing data of 5, 102 individuals with ASD for putative mutations in PER2 . Families identified were invited to complete sleep phenotyping consisting of a structured interview and two standardized sleep questionnaires: the Pittsburgh Sleep Quality Index and the Morningness‐Eveningness Questionnaire. From 5, 102 individuals with ASD, two nonsense, one frameshift, and one de novo missense PER2 variants were identified (0.08%). Of these four, none had a diagnosed sleep disorder. Three reported either a history of, or ongoing sleep disturbances, and one had symptoms highly suggestive of FASPS1 (as did a mutation carrier father without ASD). The individual with the missense variant did not report sleep concerns. The ASD and cognitive profiles of these individuals varied in severity and symptoms. The results support a possible role of PER2 ‐related circadian rhythm disturbances in the dysregulation of sleep overall and sometimes FASPS1. The relationship between dysregulated sleep and the pathophysiology of ASD require further exploration.